Kuat Tekan Dan Porositas Beton Pcc Menggunakan Crumb Rubber Dan Abu Sekam Padi Dengan Air Gambut Sebagai Mixing Dan Curing Water - Arief Rijaldo Fajri; Monita Olivia; Gunawan Wibisono (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
This study investigates the effect of peat water used on concrete with crumb rubber and rice husk ash as a mixing and curing water. The tests carried out were compressive strength and porosity for 28 days of curing. PCC concrete and PCC with crumb rubber and rice husk ash (PCC-CR-RHA) mixed and cured by clean water as a control, while the other variation were PCC-Peat and PCC-CR-RHA-Peat that are mixed and cured by peat water. PCC-CR-RHA concrete contains 5% of crumb rubber from mass of fine aggregate and 10% of rice husk ash from mass of cement. The results showed that the average compressive strength of both PCC and PCC-CR-RHA with clean water at 28 days were 35,43 MPa, while peat concrete were 16,1% lower with value at 29,72 MPa. The porosity of the specimens with clean water were 10,4% lower than the specimens with peat water. PCC-CR-RHA concrete with peat water had 90% of compressive strength (f’c) and more durable on peat water than PCC concrete showed by porosity test. The results of tests indicated that peat water can be used for mixing and curing water on PCC-CR-RHA concrete.Keywords : Peat water, crumb rubber, rice husk ash, compressive strength, porosity, rigid pavement, peat soil